Ethics and health care quality. Philotecnia versus philanthropy - De Freitas Drumond, José Geraldo (Acta Bioethica, 2010)
The medical profession has the ethical practice of the virtue of excellence. There have been since Hippocrates two ethics: the "philotechny" and the philanthropy. The first refers to the ethics of the technique and the latter, to the humanistic ethics. Nowadays, excellence results from training ande intellectual fromation acquired along formal education whose purpose is to assist a social demand, bringin satisfaction to anyone im need of it. Modern technologies are justified only if they are conditioned to an effective improvement of life quality and health of human beings and don’t represent a form of domination and usurpation of medical culture through machines, or even patient’s submission to the ideology of scientic logic of the market, which contributes to the unjustified profits for the health industry and its disregard concerning prudent assessment of the relationship between costs, risks and potential benefits to be received by the patient.